Movement of agricultural products in the Scandinavian Iron Age during the first millennium AD: 87Sr/86Sr values of archaeological crops and animals in southern Sweden. Issue 1 (1st January 2020) - Larsson, Mikael; Magnell, Ola; Styring, Amy; Lagerås, Per; Evans, Jane
ABSTRACT: In this paper, we examine the exchange of crops and livestock through the application of strontium ( 87 Sr/ 86 Sr) isotope analysis on cereal grains and faunal tooth enamel from the regional center of Uppåkra and three nearby settlements in Scania, southern Sweden, dating to the first millennium AD. Around a third of the fauna have non-local 87 Sr/ 86 Sr values, indicating the import of livestock from several different regions. After cleaning, almost all of the cereal grains have non-local 87 Sr/ 86 Sr values, which is surprising given the nearby abundance of fertile agricultural soils. We therefore suggest considering non-locally grown crops to be those whose 87 Sr/ 86 Sr values fall outside the normal distribution; if this approach is used, around 20% of the analyzed crop samples are interpreted as having grown non-locally. This study demonstrates the potential of combining strontium isotopic data of archaeobotanical and zooarchaeological material for gaining insights into the movement of agricultural products in prehistory. GRAPHICAL ABSTRACT: